A facile "dark"-deposition approach for Pt single‐atom trapping on facetted anatase TiO2 nanoflakes and use in photocatalytic H2 generation. (20th April 2022) - Cha, Gihoon; Mazare, Anca; Hwang, Imgon; Denisov, Nikita; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdeněk; Zoppellaro, Giorgio; Tesler, Alexander B.; Spiecker, Erdmann; Schmuki, Patrik
Abstract: In recent years, single-atom (SA) catalysts have become strongly investigated in electrocatalysis and increasingly also in photocatalysis. Here we demonstrate that single-crystalline anatase TiO2 nanoflake (NF) layers after a facile thermal air annealing process provide suitable anchoring sites for Pt SAs. Remarkably, such air annealed (001) faceted single-crystalline TiO2 nanoflakes can trap and stabilize Pt SAs and assemblies when immersed into a Pt precursor solution for sufficient time in absence of any illumination, i.e., under "dark deposition" conditions. These decorated species act as more efficient co-catalysts for the H2 evolution reaction, compared to the classical Pt nanoparticles (NPs). Here we show that such single-crystal-based TiO2 photocatalyst, decorated with Pt SAs, can display a 4-fold increase in photocatalytic H2 production at a lower Pt loading than observed for a classical Pt nanoparticle Pt/TiO2 arrangement. Graphical abstract: Image, graphical abstract